2016
DOI: 10.1089/ham.2016.0024
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for and Against Genetic Predispositions to Acute and Chronic Altitude Illnesses

Abstract: MacInnis, Martin J., and Michael S. Koehle. Evidence for and against genetic predispositions to acute and chronic altitude illnesses. High Alt Med Biol. 17:281-293, 2016.-Humans exhibit marked variation in their responses to hypoxia, with susceptibility to acute and chronic altitude illnesses being a prominent and medically important example. Many have hypothesized that genetic differences are the cause of these variable responses to hypoxia; however, until recently, these hypotheses were based primarily on sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 134 publications
(121 reference statements)
0
24
0
Order By: Relevance
“…However, these genes have been related to chronic mountain sickness, and as far as we know, no direct evidence between these genes and AMS has been proposed. 38 39 Although it seems likely that genetics plays a role in the development of AMS, we cannot fully decide whether the observed differences between Tibetan and Han Chinese students can be explained by genetic background. It has been reported that lowlanders with a pre-exposure to high altitude may establish some degree of physiological adaptation, thus resulting in a reduction in the incidence and severity of AMS when they reascend to high altitude.…”
Section: Discussionmentioning
confidence: 95%
“…However, these genes have been related to chronic mountain sickness, and as far as we know, no direct evidence between these genes and AMS has been proposed. 38 39 Although it seems likely that genetics plays a role in the development of AMS, we cannot fully decide whether the observed differences between Tibetan and Han Chinese students can be explained by genetic background. It has been reported that lowlanders with a pre-exposure to high altitude may establish some degree of physiological adaptation, thus resulting in a reduction in the incidence and severity of AMS when they reascend to high altitude.…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting that trait STAI Y-2 scores and not state STAI Y-1 scores, taken at the study baseline altitude of 848m, were predictive of future risk of severe AMS. This is perhaps not surprising, given that susceptibility to AMS appears to be a relatively stable individual trait with increasing evidence for a genetic predisposition that can be influenced by additional factors such as ascent profile [ 28 30 ]. We found that trait anxiety and STAI Y-2 questions, as opposed to STAI Y-1 was a predictor of future AMS given its representation of more stable individual trait anxiety levels [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of numerous polymorphisms of the HIF1A gene and dependent genes indicates some genetic determinism of tolerance to hypoxia [ 16 , 80 ]. The presence of HIF1A gene polymorphisms in humans, which determines the high level of HIF-1α expression and functional activity, can contribute to growth in an aerobic capacity and the organism’s adaptation to hypoxia and physical activities [ 81 , 82 , 83 , 84 ].…”
Section: Cellular Response To Hypoxic Exposurementioning
confidence: 99%
“…Oxygen deficiency is one of the key factors in the development of infectious, inflammatory, and tumor diseases [ 1 , 2 , 3 , 4 , 5 , 6 ]. It is known that basic tolerance to hypoxia in humans and various animal species differs [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The differences in basic tolerance to oxygen deficiency can determine the predisposition to the development of hypoxia-related disorders.…”
Section: Introductionmentioning
confidence: 99%